FRI0314 Different serum cytokine profiles reflect anti-neutrophil cytoplasmic antibodies (ANCA) specificity in patients with anca-associated vasculitis. (15th June 2017) - Berti, A; Warner, R; Johnson, K; Cornec, D; Schroder, D; Kabat, B; Merkel, PA; Langford, CA; Hoffman, GS; Kallenberg, CG; Seo, P; Spiera, R; et al.
Abstract : Background: Evidence supporting the classification of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) based on ANCA type is accumulating. 1 Objectives: To evaluate serum cytokine profiles in patients with AAV classified by ANCA specificity (proteinase 3 (PR3)-ANCA versus myeloperoxidase (MPO)-ANCA) or by clinical diagnosis (granulomatosis with polyangiitis (GPA) versus microscopic polyangiitis (MPA)) and clinical phenotypes. Methods: An antibody array testing 30 soluble mediators, already shown to be implied in the pathogenesis of AAV, was performed in each patient with active AAV at inclusion in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial, as previously described. 2, 3 By means of Wilcoxon signed rank test for univariate analyses, we analyzed the association of levels of these cytokines with ANCA specificity, clinical diagnosis, and distinct clinicopathologic phenotype categories derived from the BVAS/WG items recorded at the time of enrollment (capillaritis, granulomatous manifestations, renal involvement, and alveolar hemorrhage; new diagnosis and relapsing disease), as described. 4 Results: All cytokines tested (see Figure 1 and legend for the complete list), except for RANTES, ACE, bFGF and VCAM-1, were significantly increased in the RAVE cohort when compared to healthy controls ( p <0.05). Median Birmingham vasculitis activity score and steroid use at screening did not significantly differ between PR3-AAV and MPO-AAV, and between GPA and MPA. Within both ANCA specificities, levels of 9 mediators were significantly higher in PR3-AAV (IL-6, NGFb, GM-CSF, IL-15, IL-18, IL-18Bb, sIL-2Ra, IL-8, TARC; p <0.05), compared to 5 different cytokines that were higher in MPO-AAV (sIL6R, NGAL, sICAM-1, VCAM-1, sTNFR II; p <0.05). In contrast, only 4 cytokines (GM-CSF, IL-15, IL-18, sIL-2Ra) were higher in GPA than MPA, and 1 (NGAL) was higher in MPA than GPA ( p <0.05). The association of the majority of cytokines was stronger with ANCA specificity than with the clinical diagnosis (Figure 1 ). Similarly, the defined clinical phenotypes were also not separated by cytokine signatures as clearly as the ANCA specificity was ( data not shown ). Restricting the analysis to newly-diagnosed patients (n=90) showed the most significant cytokine profile differences associated with PR3-AAV (Figure 1 ). Conclusions: Cytokine profiles separate patients more clearly by ANCA specificity than by clinical diagnosis, suggesting important differences in underlying pathophysiology and validating stratification of patients by ANCA specificity for treatment trials. References: Cornec D et al. Nat Rev Rheumatol. 2016 Oct;12(10):570–9. Monach PA et al. Ann Rheum Dis. 2013 Aug;72(8):1342–50. Stone J et al. N Engl J Med. 2010 Jul 15;363(3):221–32. Fussner LA et al. Arthritis Rheumatol. 2016 Jul;68(7):1700–10. Disclosure of Interest: None declared